An experimental study into the net cross-sectional failure of damaged plates with holes for different steel grades and temperatures (Fracture and Structural Integrity, 2025)
This study reports an experimental investigation on the applicability of the net cross-sectional resistance rules of Eurocode 3 for steel plates with different bolt-hole configurations and steel grades, when relatively small fatigue cracks are present at the edge(s) of the holes. Previous studies have confirmed that the considered design rule is on the safe side. Moreover, part of this safety margin accounts for the potential occurrence of relatively small fatigue cracks.Two steel grades are considered, namely S275JR and S700MC. Therefore, in addition to previous studies, a relatively high steel grade is considered. Moreover, some tests were carried out on cooled specimens to get an impression of the effect of low temperatures on the failure mechanism.  The experimental results demonstrate that relatively small cracks (
Keywords: Capacity design; Structural steel; Eurocode 3; Failure assessment